A Non-interventional Study on Vismodegib for Basal Cell Carcinoma With A Treat-To-Target Regimen In Swedish Patients - Niels Bendsöe; John Paoli; Karin Söderkvist; Bertil Persson; Christina Halldin; Linda Ihrlund; Maria Wolodarski (Mattioli1885, 2023)
Introduction: Real-life data on vismodegib in advanced basal cell carcinoma (aBCC) are limited. Optimal treatment duration is left to the discretion of the physician. Objectives: To assess the effectiveness, safety and treatment pattern for vismodegib in aBCC in clinical practice. Methods: In this multicenter, non-interventional, prospective study, 49 Swedish patients planned for vismodegib treatment were included. The treatment pattern observed was treatment until remission, allowing unlimited discontinuations/pauses. Results: The majority of patients (93.8%), discontinued at least once during the study. Compared to earlier studies there was a decrease of more than 2 months with actual drug intake, reducing the patients burden and costs, at the same time as a high number of responses were seen (87.8%). Median progression-free-survival was 16.7 months, and 90% of the patients were alive at 13.3 months. Ten patients were re-challenged with vismodegib at recurrence or progression, resulting in five partial remissions and three complete remissions.  Conclusions: Clinical response rates with vismodegib for aBCC were similar to those of similar trials despite a shorter and more intermittent treatment duration. The majority of re-challenges lead to partial or complete remissions.